Groundnut phylloplane microbiome: Characterisation and antagonism against groundnut leaf blight pathogen, Alternaria alternata - Priyadarshini, P; Senapati, A K; Kumar, Sandeep; Tripathy, A (Indian Journal of Plant Protection, 2021)
Groundnut (Arachis hypogea) is an important source of edible oil and protein. Diseases caused by more than 55 pathogens are one of the major constraints in attaining high production of groundnut as they reduce the yield to the tune of 70%. Among them, leaf blight of groundnut caused by Alternaria alternata is a major disease causing 22% of pod reduction and 63% of fodder reduction depending upon the severity. Use of chemicals for plant disease management has caused severe environmental deterioration and many health hazards. Recent understandings have changed the concept of plant health and it has been suggested that associated microbes can be used for better health of plants. Therefore, integrating natural beneficial microbiome in plant disease management is one of the best strategies to feed ever growing world population amidst changing global climate. In the present investigation phylloplane microflora of groundnut were studied for their antagonistic potential against A. alternata causing leaf blight of groundnut. Five each of bacteria and fungi exhibiting constant association with the host phylloplane were identified to be Enterobacter cloacae, Paenibacillus sp., Erwinia sp., Micrococcus luteus, Bacillus subtilis, C. gloeosporioides, Fusarium solani, F. pallidoroseum, Aspergillus fumigatus and Aspergillus flavus. In-vitro study using dual culture technique revealed A. flavus and Fusarium solani as the most potent antagonistic fungal microbes inhibiting 84.18% and 73.2% growth of the pathogen (A. alternata) respectively. Similarly, among bacterial population B. subtilis exhibited the highest degree of antifungal activity followed by M. luteus, inhibiting 78.37% and 76.74% growth of the test fungus respectively. To the best of our knowledge, this is the first such study where phylloplane microbiome has been shown to be effective for the management of leaf blight of groundnut. Further studies in this regard at laboratory and field conditions can lead to commercialization of these phylloplane microbes which will offer an eco-friendly and sustainable management of Alternaria leaf blight of groundnut.